IMPROVING STUDENTS’ WRITING SKILL BY USING SCRAMBLE SENTENCE METHOD - M. Afrizal (Jurnal Pendidikan Almuslim, 2016)
This thesis entitled Improving Students’ Writing Skill by Using Scramble Sentence Method (A Collaborative Classroom Action Research To the Second Years Students of SMP Negeri 3 Bireuen). The problems of the research are (1) Can the use of Scramble Sentence Method improve the students’ writing skill to the second year students of SMP Negeri 3 Bireuen?, and (2) Can the use of Scramble Sentence Method give motivation to the students?. Based on research problems, the purposes of the research are (1) To find out whether the Scramble Sentence Method can improve the students’ writing skill, and (2) To find out whether the Scramble Sentence Method can give motivation to the students in learning writing. In implementing, this research was designed in collaborative classroom action research because the main purpose of this research was to improve the students’ writing skill of SMP Negeri 3 Bireuen. There were two cycles consisted of planning, implementing, observing and reflecting. In cycle I, the action was done in three meetings, but it was not successful because the students’ mean score only 68,64 and it did not reach the criteria of success yet. So, the researcher revised the plan and continued to the cycle II. In cycle II, the action also was done in three meetings and it was success based on the students’ mean score had increased became 88,21. Based on the result of questionnaire, the researcher got the mean score of students’ responses was 4,74 and it was categorized strongly agree. It means that most of students were motivated in learning writing through Scramble Sentence Method. So, based on the result finding, the researcher concluded that this research was success in improving and motivating the students in learning writing through Scramble Sentence Method. Key Words: Writing, Scramble Sentence Method